Seasonal changes in plasma levels of sex hormones in the Greater Rhea (Rhea americana), a South American ratite with a complex mating system - Valdez, Diego Javier (2014)
Seasonal rhythm in sex hormones has been extensively studied in birds, as well as its relationship with the type of mating system. The Greater Rhea (Rhea americana), a South American ratite species, reproduces seasonally and has a complex mating system: female-defense polygyny and sequential polyandry. The present study aimed at analyzing the endocrine basis of reproduction in this species and its relationship with its mating system. We used HPLC and electrochemiluminescence techniques to identify and measure plasma testosterone and estradiol levels. Annual oscillations in sex hormones, testosterone and estradiol, in adult males and females were observed. Lower levels of these hormones were exhibited during the non reproductive season (February to July), whereas their maximum values were reached in September for males and November-December for females. These fluctuations reflect the seasonal changes in gonadal function. By contrast, no significant sex hormones oscillations were observed in juvenile males and females (negative control of seasonal changes). Greater rheas maintain high testosterone and estradiol levels throughout the reproductive period. The high testosterone levels during incubation and chick rearing did not inhibit parental behavior in males, which appears not to conform to the ??Challenge Hypothesis??. In females, the high estradiol levels throughout the reproductive season would be needed to sustain their long egg-laying period.